Survey of new attack models on Cloud Infrastructure (International Journal of Engineering and Computer Science, 2018)
Cloud Computing is currently most useful technol- ogy around the globe which offers an innovative business models for infrastructure to the enterprise , software services to the end users and the easy to deploy platform to the developer on Internet using virtual machine , for the quick and easy accessibility. It     is Internet driven technology, which gives pool of resources such as Storage , Network , Application on demand basis. As the technology is driven over the Internet and virtual machine and allow resource pooling their are various kind of security problem arise relate to the model architecture, multi-tenancy, elasticity, data confidentiality, authentication and authorization. Various kind of attack could happen in cloud infrastructure ,as there      is no exact definition about the attack and attack  model  but here we try to group into a various levels eg. Network level, host level and application level and few other attacks and the solution to prevent the attacks. In this paper we will discuss about the different kind of attacks and solution on cloud services